The corporate calendar and the timing of share repurchases and equity compensation - Ingolf Dittmann; Amy Yazhu Li; Stefan Obernberger; Jiaqi Zheng (Tinbergen Institute, 2022)
This study examines whether the CEO uses share repurchases to sell her equity grants at inflated stock prices, a concern regularly voiced in politics and media. We find that the timing of buyback programs and equity compensation, i.e., the granting, vesting, and selling of equity, is largely determined by the corporate calendar through blackout periods and earnings announcement dates. As a consequence, share repurchases and equity compensation are positively correlated. This correlation disappears once we account for the corporate calendar and should thus not be interpreted causally. Our results do not support the conclusion that CEOs systematically misuse share repurchases at the expense of shareholders. To the contrary, equity compensation increases the propensity to launch a buyback program when buying back shares is beneficial for long-term shareholder value.
Keywords: G14; G35; M12; M52; 330; Payout policy; share repurchases; equity-based incentives; short-termism